On the application of colour schlieren on supersonic jets - Teo, Joel Han Hong (2018)
A conical convergent-divergent (CD) nozzle of design exit Mach 1.5 and diameter 5mm was designed and manufactured. The supersonic flow produced by the nozzle was experimentally investigated using the Z-type colour schlieren technique at three nozzle pressure ratios (NPR) of NPR= 6.44, NPR= 5.08 and NPR= 3.72. The supersonic flow was tested at three conditions and the conditions were namely freely exhausting jet, impinging jet on a flat plate and impinging jet on an orifice. Two separation distances were tested in the conditions of impinging jet on a flat plate and impinging jet on an orifice to investigate the effects of varying separation distance. The resultant colour schlieren images obtained experimentally were analysed qualitatively and an Abel transform inversion algorithm was later applied to obtain quantitative measurements of the density gradient in the images. The NPR and separation distance were found to be the determining factor for the formation of shock diamonds and the density gradient in the flow.